The relevance of certifications and business practices in linking smallholders and large agro-businesses in Sub-Sahara Africa - Linda Kleemann (Kiel Institute for the World Economy (IfW), 2015)
Smallholders often have to certify according to international standards and produce under contract for large agro-businesses to access the export market. While mostly positive effects for the farmers have been found for contracts and certifications, little is known about the role of individual firm behavior and certifications in shaping farmer-agro-business relationships and contract success. This is what this article does. Data of 386 smallholders in the pineapple export sector in Ghana is analyzed quantitatively and enriched by a detailed case study of a large-scale agro-business in Ghana called Blues Skies. The results show that certification is an agent of change in farmer-agro-business relations. Building trust and aligning expectations of farmers and firms is important for success. Additionally, individual firm behavior matters more than taken into account in previous research. Our case study shows that three 'R', reliability, reputation and respect, constitute the basis for contract relationships that benefit all.
Keywords: 330; contract farming; certification; smallholders; Ghana; firm behavior